Zwitterionic Coatings: Zwitterionic‐Coated "Stealth" Nanoparticles for Biomedical Applications: Recent Advances in Countering Biomolecular Corona Formation and Uptake by the Mononuclear Phagocyte System (Small 13/2014). Issue 13 (July 2014) - García, Karina Pombo; Zarschler, Kristof; Barbaro, Lisa; Barreto, José A.; O'Malley, William; Spiccia, Leone; Stephan, Holger; Graham, Bim
<x xml:space="preserve">Abstract</x> The development of nanoparticle assemblies for in vivo applications is hampered by the fact that most nanoparticles are scavenged by the mononuclear phagocyte system, in a process commencing with the rapid adsorption of serum proteins, including antibodies, to their surface. On page 2516, L. Spiccia, H. Stephan, B. Graham, and colleagues summarize the recent efforts to develop zwitterionic‐coatings, which resist the formation of such a "biomolecular corona", providing promising platforms for future nanomedicine design. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>